Restorative justice - how can this technique be adopted from micro level use in pastoral areas of school life to being used on a whole school level in which all members of staff are participants - Needham, Gemma (2013)
This study will investigate key elements for successful transition from the micro-level use of restorative justice to the macro-level use of the concept. This study will identify key points to consider for successful school improvement as well as for moves towards whole-school use of restorative justice. A questionnaire will be used to improve understanding in a number of areas; firstly, staff perceptions of and attitudes towards school improvement at School A; secondly, their understanding of restorative justice at this time; thirdly, staff perceptions of and attitudes towards the use of restorative justice at School A; and finally, possible methods of continuing professional development with specific regard to restorative justice. Recommendations from this study will link to staff training, leadership, integration through the school’s behaviour policy, and development of student understanding. The study will find that ultimately success relies on all implementations being context-specific and as such, the recommendations aim to offer School A context-identified strategies to support successful transition.